An automatic segmentation method for scanned images of wheat root systems with dark discolourations - Gocławski, Jarosław; Sekulska-Nalewajko, Joanna; Gajewska, Ewa; Wielanek, Marzena (Zielona Góra: Uniwersytet Zielonogórski)
The analysis of plant root system images plays an important role in the diagnosis of plant health state, the detection of possible diseases and growth distortions. This paper describes an initial stage of automatic analysis - the segmentation method for scanned images of Ni-treated wheat roots from hydroponic culture. The main roots of a wheat fibrous system are placed separately in the scanner view area on a high chroma background (blue or red).
Keywords: root system image; segmentation; skeleton; root discolourations; fuzzy c-means clustering